Relationships of Arabic and Malay Language in The Syair Gulong Ketapang West Kalimantan - ardiansyah ardiansyah (Arabic Education Program IAIN Pekalongan, 2019)
Malay and Arabic have a relationship that influences the emergence of literary works including poetry. Syair Gulong is one of the many Malay literary works that have a relationship with Arabic. This relationship is inseparable from the circle of Islamic religiosity in both languages. This study aims to reveal the relations between the two languages ​​in Syair Gulong. The form of the relation referred to in this study is the emergence of absorption words with various forms and phonological changes in syair gulung. This research concludes that the uptake words in syair gulong have a relationship between Arabic and Malay in the form of word uptake, solid uptake, and translation uptake. However, this language relation cannot be separated from the appearance of absorption words that undergo phonological changes.